The study of association between maternal serum magnesium levels and preterm labour in a tertiary care hospital - Anand, Shifali; Hak, Jyoti; Prashar, Niveditaa; Gandotra, Nikita; Jaggi, Rohini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Serum magnesium level in pregnancy is a valuable tool to find out preterm onset of labour. In the asymptomatic group, greater surveillance and administration of steroids, tocolytics and transfer to a higher centre wherever necessary has to be done with mothers with low serum magnesium level. The objective of the study is to find association between serum magnesium levels and women with preterm labour, and to compare these values with those patients who have a term delivery. Methods: The subjects included 100 pregnant women with preterm labour (cases) between 28 and 37 weeks gestation (Group A) and similar number of pregnant women with term labour (controls) between 37 and 40 weeks (Group B). Inclusion criteria for cases was singleton pregnancy, painful uterine contractions more than two in 30 minutes, intact fetal membranes, cervical dilatation (at least 1 cm) and effacement (80%). Serum magnesium levels were done in both the groups. Patients were followed until delivery. Routine antenatal investigations were done. Serum levels of magnesium were estimated by Erba’s semi auto-analyser. Results: 62% patients in Group A were from rural areas. More patients in Group A (70%) were from low socioeconomic class. More women in Group A were anaemic (44%). Mean value of hemoglobin in Group A was 9.93gm/dL. More patients in Group A had muscle cramps (89%). VLBW (<1500gm) neonates were more in Group A (21%). Also, LBW (1500-2499gm) neonates were more in Group A (60%). Mean neonatal birth weight in Group A (1907.3gm) was less. Neonatal morbidity and mortality was observed significantly more in Group A. Mean serum magnesium was less in Group A. Mean serum magnesium levels in primi and multigravida patients were less in Group A. Moreover, mean serum magnesium levels were less in urban and rural patients in Group A. Mean serum magnesium levels were less in normal and overweight patients in Group A. Also, mean serum magnesium levels were less in patients with cervical dilatation <3cm and >3cm in Group A. Conclusions: Low maternal serum magnesium level is associated with preterm labour. Patients with preterm labour have significantly low serum magnesium level when compared with labour at term.